Effects of a 10-month neuromuscular training program on strength, power, speed, and vault performance in young female gymnasts - Moeskops, S.; Oliver, J. L.; Read, P. J.; Haff, G.; Myer, G. D.; Lloyd, R. S. (Medicine & Science in Sports & Exercise, 2022)
Purpose This study aimed to evaluate a 10-month neuromuscular training (NMT) intervention on isometric and dynamic kinetics, standing long jump (SLJ) distance, speed, and sport-specific performance.